Poligami dan Penguatan Hak-hak Perempuan (Reformasi Hukum Keluarga Islam di Mesir dan Indonesia) - Amri, Aulil; Syafitri, Anesia; Trisna, Albirra; Qanita; Fahri, Said (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
One of the reasons for changing family law in the Islamic world is to enhance the rights of women, who often face discrimination. This change is connected to its historical background and the madhhab (interpretation) embraced by the governing body. Egypt first made adjustments to family law with Law No. 25 in 1920 and again in 1929. A key aspect that was modified in both nations was polygamy. In Indonesia, the initial adjustment to family law occurred with the Marriage Law of 1974, which was backed by the KHI. While both nations permit polygamy, it is governed by specific criteria that a husband must fulfill to engage in this practice. The objective of this research is to examine the reforms of Islamic family law in Egypt and Indonesia concerning the enhancement of women's rights, especially in relation to polygamy, and to assess how these reforms have influenced the status of women in society. This analysis employs a normative legal research methodology, utilizing a framework that combines Islamic law with positive law evaluation. Data for this research was collected through literature reviews and an examination of Islamic family law documents from Egypt and Indonesia. Findings from the study indicate that reforms in Islamic family law in both Egypt and Indonesia have resulted in meaningful advancements in supporting women's rights. In Egypt, legislation that has made polygamy requirements stricter and granted wives the privilege to initiate divorce has improved the safeguarding of women's rights. In Indonesia, the Marriage Law affecting polygamy has similarly empowered wives with the ability to seek divorce and has tightened the criteria for polygamy. Nevertheless, this research also identifies that the enforcement of these laws remains inadequate, and a significant barrier continues to be the lack of public understanding regarding women’s rights.